The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1136/bjsm.26.4.276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeine on maximal strength and power in élite male athletes.

Abstract: Computerized testing of 20 élite male athletes was performed to determine the effect of 7 mg kg-1 caffeine on strength and power of the knee extensors and flexors. Subjects received counterbalanced administrations of either caffeine or a placebo on two separate occasions. Peak torque (T) was measured for knee extension (ET) and flexion (FT) at angular velocities of 30 degrees, 150 degrees and 300 degrees s-1. Additionally, performance for the first 125 ms (TAE) and power (W) were recorded during 300 degrees s-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 16 publications
4
44
1
2
Order By: Relevance
“…[16][17][18] Findings have suggested direct effects on muscle excitationcontraction coupling and motor unit recruitment, which are independent from those related to metabolic efficiency. [18][19][20] Unfortunately, most of the aforementioned studies have focused on maximal isometric strength, whereas the effect of caffeine on neuromuscular function during dynamic contractions at different speeds has not been investigated thoroughly.…”
Section: -15mentioning
confidence: 96%
“…[16][17][18] Findings have suggested direct effects on muscle excitationcontraction coupling and motor unit recruitment, which are independent from those related to metabolic efficiency. [18][19][20] Unfortunately, most of the aforementioned studies have focused on maximal isometric strength, whereas the effect of caffeine on neuromuscular function during dynamic contractions at different speeds has not been investigated thoroughly.…”
Section: -15mentioning
confidence: 96%
“…possibly because of the limited number of investigations and different protocols used (3,9,27,33,35,36,56,64).…”
Section: Introductionmentioning
confidence: 99%
“…In sprint and power events that rely mainly on the phosphogen system (#10 seconds), caffeine improved peak power output, speed, and isokinetic strength (3,36,56); however, in events that heavily rely on the glycolytic system (15 seconds to 3 minutes), no improvements were found with caffeine use, and in fact, it may have been detrimental to performance during repeated bouts of exercise (27,64). One study showed a 7% increase of peak power output during 6-second Wingate testing with consumption of 250 mg of caffeine (3), whereas another recent study showed improvements of intermittent sprint ability (during 4-second sprints) in soccer players when 6 mgÁkg 21 of caffeine was ingested (56).…”
Section: Introductionmentioning
confidence: 99%
“…Estudios concluyen que la cafeína a dosis pequeñas no ejerce ningún efecto ergogénico sobre la función muscular en condiciones anaeróbicas 19 ; mientras en otro estudio se encuentra que a una dosis de 7 mg kg-1 la fuerza aumenta por la ingestión de cafeína 21 , a dosis de 6mg/Kg el aumento en la fuerza máxima es de 3,5% sin cambios en el reflejo H, concluyendo los autores que la cafeína actúa tanto periféricamente, como de forma supraespinal 18 . En otro estudio la fuerza máxima se incrementó en un 3,8% 22 y finalmente otro estudio encontró a una dosis de 6 mg/Kg un cambio en la fuerza equivalente al 17% y concluyen que el efecto de la cafeína esta sobre la reducción de la sensación de fuerza 23 .…”
Section: Discussionunclassified